Phylogeny of the old and fragmented genus Austrocoenosia Malloch reveals new evidences on the morphology and evolution of the genera Coenosia Meigen and Neodexiopsis Malloch (Diptera: Muscidae) - Patitucci, Luciano Damián (2023)
Coenosiini (Diptera: Muscidae) is a large cosmopolitan tribe of muscids, within which Coenosia Meigen and Neodexiopsis Mallochare the genera with the largest number of species. In this work, we revised for the first time, all the species placed by Malloch (1934)under Austrocoenosia, an endemic genus from the Andean Patagonian Forests, whose species are now placed in Coenosia and Neodexiopsis. We provide detail redescriptions for eight species placed by Malloch (1934) under Austrocoenosia, and decribed two newspecies (Coenosia delneneo sp. nov. and Coenosia patagonica sp. nov.), with high quality photographs detailing new structures ofthe male and female terminalia. To establish the position of the species of Austrocoenosia with respect to Coenosia and Neodexiopsis,we made a phylogenetic analysis using implied weighting for 36 taxa and 132 morphological characters of adults, including male andfemale genitalia. We recovered all species of Austrocoenosia as Coenosia species. We propose the following nomenclature actions:Austrocoenosia as a junior synonymy of Coenosia (syn. rest.); Coenosia brevicornis (Malloch) (comb. nov.), Coenosia dubia (Bigot) (comb. rest.); Coenosia hucketti, Pont (nom. nov.) and Coenosia nigerrima (Malloch) (comb. rest.). We also propose Coenosiaspumicola Pont as an unplaced species of Coenosia sensu lato. Finally, we updated the geographic distributions for all species andobserved several new male and female terminalia structures, which enriched the discussion of the genera and the tribe.